Spatiotemporal patterns of urban sprawl and its relationship with economic development in China during 1990–2010. (September 2018) - Zhang, Charlie; Miao, Changhong; Zhang, Wenzhong; Chen, Xiaohong
Abstract: Given the fact that China has been experiencing rapid urbanization since the 1980s, limited empirical research has analyzed the spatial patterns of urban land expansion across Chinese cities using national data sets. This article attempts to explore evidence of urban sprawl and its relationship with levels of economic development using novel geospatial data on urban area boundaries and development densities for all Chinese cities. Different from existing studies, we used a decomposition approach to examine the differences between the 1990 urban boundaries and their newly developed suburbs (1990–2010) in population density and road intersection density, two key characteristics of urban sprawl. The main results show that Chinese cities have experienced dramatic increases in built-up areas but substantial decreases in development densities in the newly urbanized areas in comparison to their inner city counterparts, signifying concrete evidence of urban sprawl. Moreover, results from regression analyses indicate that a city's economic development level was positively related to urban land expansion after controlling for confounding factors, largely due to the nature of China's land-centered urbanization and economic development strategies. Findings from this article can help raise awareness about the staggering reality of urban land expansion across Chinese cities and urge urban planners and policymakers to tighten their rural-to-urban land conversion systems and curb urban sprawl.